2013
DOI: 10.1002/cbm.1889
|View full text |Cite
|
Sign up to set email alerts
|

The Index Offence Representation Scales; a predictive clinical tool in the management of dangerous, violent patients with personality disorder?

Abstract: Background Forensic professionals attach considerable importance to their patient's description of his or her index offence which is frequently used to inform the patient's management and predict future behaviour. However, despite the cardinal importance of the index offence there is no systematic approach to examining and formulating the patient's offence narrative. Aim To examine whether a clinical tool, which tapped into the patient's capacity to mentalize, could be developed from the index offence narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In this study, we used a cross-sectional design based on the administration of two clinical interviews in a sample of detained male stalkers in two northwest Italian correctional facilities. The research design focused on the textual data gathered from the AAI (George et al, 1985) and the Index Offense Interview (IOI; McGauley et al, 2013), which we analyzed at two levels using the standard coding procedure and interpretative phenomenological analysis (IPA; Brocki & Wearden, 2006;Levitt et al, 2017), within the context of qualitative analyses. We adopted the qualitative approach because it is traditionally used in clinical psychology (e.g., Silverman, 2016) and in attachment studies (Bateman & Fonagy, 2016;Main, 1993) to shed light on subjects' narrative mental content.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used a cross-sectional design based on the administration of two clinical interviews in a sample of detained male stalkers in two northwest Italian correctional facilities. The research design focused on the textual data gathered from the AAI (George et al, 1985) and the Index Offense Interview (IOI; McGauley et al, 2013), which we analyzed at two levels using the standard coding procedure and interpretative phenomenological analysis (IPA; Brocki & Wearden, 2006;Levitt et al, 2017), within the context of qualitative analyses. We adopted the qualitative approach because it is traditionally used in clinical psychology (e.g., Silverman, 2016) and in attachment studies (Bateman & Fonagy, 2016;Main, 1993) to shed light on subjects' narrative mental content.…”
Section: Methodsmentioning
confidence: 99%
“…Deficits in social cognition in general and the capacity to link mental states to behaviour in particular are commonly identified in association with antisocial behaviour [28, 29]. Some (but not all [30]) individuals with ASPD show a blend of perspective-taking problems and difficulty in reading others’ mental states [31–37]; this is consistent with the mentalization literature’s deficit theory as well as other theories of antisocial behaviour [38, 39]. It has been suggested that one pathway to adult antisocial personality leads from early child conduct disorder via alcohol abuse in early adolescence to compromised function (and maturational delay) of the cognitive control system, of which mentalization is a part [40, 41], and which matures throughout adolescence and into early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two clinical interviews were administered to the part of the sample who agreed. These instruments were the AAI (George et al, 1985) and the IOI (McGauley et al, 2013), which were recorded, transcripted verbatim, and then analyzed applying the RFS (Fonagy et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Veglia and Castellino (2013), in a sample of 27 imprisoned Italian sex offenders, from RFS applied to both attachment and crime narratives, found clearly inadequate RF for the age and intelligence of the participants, and in some cases, negative, absent, weird, or distorted RF. Especially, when they are were telling their offence in the Index Offence Interview (IOI; McGauley et al, 2013), the RF tended to decline, when the participants were asked to reason on what they thought or felt when aggressive, about what they believed that the victim could have felt or thought. They showed, in these reports, a deep disconnection between emotions, desires, intentions, beliefs, and actions.…”
Section: Dissociation In Stalker Populationmentioning
confidence: 99%